How sex work becomes an option: Experiences of female sex workers in Kerman, Iran. Issue 1 (2nd January 2016) - Karamouzian, Mohammad; Foroozanfar, Zohre; Ahmadi, Azal; Haghdoost, Ali Akbar; Vogel, Joanna; Zolala, Farzaneh
Abstract: Sex work is rarely an occupation of choice for Iranian women and is often described as a last resort. While several factors play a role in creating an environment where individuals become involved in sex work, female sex workers' experiences regarding entry into sex work in Iran are poorly understood. In this qualitative study, a convenience sample of 24 participants was recruited from a drop-in centre for vulnerable women in Kerman, Iran. Through in-depth interviews, participants were asked about their personal lived experiences of initiating sex work. Grounded theory was used to analyse findings from this research. We learned that major factors impacting on women's initiation into sex work circulated around their vulnerability and chronic poverty. Participants continued to sell sex due to their limited opportunities, drug dependence and financial needs. Improving sex workers' economic status could be a vital intervention in providing vulnerable women with options other than sex work. Female sex workers should be provided with government support and educational programmes delivered through special centres. Despite the illegal status of their work, sex workers' needs should be recognised across all aspects of policy and legislation.